Tracer Study Analysis to Improve the Quality of Graduates of the PTI Study Program at UM Kendari - Hasim, La Ode; Cahyani, Gita; M, Mirnawati; Felisa, Agista Salsa; Dermawan, Imam; Razilu, Zila (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the results of a tracer study of alumni from the Information Technology Education Study Program (PTI) at Universitas Muhammadiyah Kendari. The purpose is to evaluate the waiting period for employment, the relevance of the curriculum to industry needs, user satisfaction with graduates, and the alignment of alumni competencies with job requirements. This research uses a quantitative descriptive approach with 52 alumni respondents. Data were collected through an online questionnaire based on national tracer study guidelines. Statistical techniques used include percentage analysis, mean, median, mode, variance, standard deviation, Pearson correlation, and regression analysis to measure the relationship between academic performance and employment outcomes. The findings show that the average waiting time for alumni to obtain their first job is 4.03 months, with a median of 3.45 months, indicating generally fast absorption. The relevance of the curriculum reaches an average score of 82%, categorized as very good. User satisfaction with alumni is also high, reaching 82% of the maximum score. Regression analysis indicates a positive correlation between academic achievement and job readiness. The study concludes that PTI UM Kendari graduates have good competitiveness, although curriculum improvements related to emerging technologies are still needed.